Consumer Preferences for Coconut Shell Charcoal in Suburban Indonesia - Yandri, Pitri (Universitas Prasetiya Mulya, 2013)
Suburbs in Indonesia are not only characterized by the presence of residential areas, but also trading activities. These activities exist in order to support the needs of residents for goods and/or services. The complicated process that involves pull and push factors causes the suburbs to be well-known as economically potential areas, especially for micro, small, medium and large enterprises. One example of the trading subsectors is restaurants, both micro enterprises with traditional management and franchises patterns with professional management. Most of these restaurants provide barbequed menus which consume shell coconut charcoal. Then the question arises, is the quality of those commodity is the only reason for the restaurants in using it? This paper presents the elaboration of the research on consumer preferences in a suburban area of the consumption of coconut shell charcoal. By using the Fishbein Model, it is concluded that the aspect of belief and price attribute are in the first rank, which shows that those commodity is an expensive fuel, while the second rank is quality. The rest are models and after-sales service, respectively. From the aspect of evaluation, the respondents believe that quality is in the first rank that should be improved in the future. The second is price and the rest are after-sales service, packaging and models, respectively.